Association of residency work hour reform with long term quality and costs of care of US physicians: observational study. (10th July 2019) - Jena, Anupam B; Farid, Monica; Blumenthal, Daniel; Bhattacharya, Jay
Abstract: Objective: To determine whether 30 day mortality, 30 day readmissions, and inpatient spending vary according to whether physicians were exposed to work hour reforms during their residency. Design: Retrospective observational study. Setting: US Medicare. Participants: 20% random sample (n=485 685) of Medicare beneficiaries aged 65 years or more admitted to hospital and treated by a general internist during 2000-12. Main outcome measures: 30 day mortality, 30 day readmissions, and inpatient Medicare Part B spending among patients treated by first year internists who were fully exposed to the 2003 Accreditation Council for Graduate Medical Education (ACGME) work hour reforms during their residency (completed residency after 2006) compared with first year internists with partial or no exposure to reforms (completed residency before 2006). Senior internists not exposed to reforms during their residency served as a control group (10th year internists) for general trends in hospital care: a difference-in-difference analysis. Results: Exposure of physicians to work hour reforms during their residency was not associated with statistically significant differences in 30 day mortality, 30 day readmissions, or inpatient spending. Among 485 685 hospital admissions, 30 day mortality rates during 2000-06 and 2007-12 for patients of first year internists were 10.6% (12 567 deaths/118 014 hospital admissions) and 9.6% (13 521/140 529), respectively, and for 10th year internists were 11.2% (11 018/98 811) and 10.6% (13 602/128 331), for an adjusted difference-in-difference effect of −0.1 percentage points (95% confidence interval −0.8% to 0.6%, P=0.68). 30 day readmission rates for first year internists during 2000-06 and 2007-12 were 20.4% (24 074/118 014) and 20.4% (28 689/140 529), respectively, and for 10th year internists were 20.1% (19 840/98 811) and 20.5% (26 277/128 331), for an adjusted difference-in-difference effect of 0.1 percentage points (−0.9% to 1.1%, P=0.87). Medicare Part B inpatient spending for first year internists during 2000-06 and 2007-12 was 1161 (£911; €1024) and 1267 per hospital admission, respectively, and for 10th year internists was 1331 and 1599, for an adjusted difference-in-difference effect of −46 (95% confidence interval −94 to 2, P=0.06). Conclusions: Exposure of internists to work hour reforms during their residency was not associated with post-training differences in patient mortality, readmissions, or costs of care.